Long COVID in patients with rheumatologic disease: A single center observational study - Horacio Quinones-Moya; Armando Ocampo-Del Valle; Adolfo Camargo-Coronel; Francisco Javier Jimenez-Balderas; Miriam Berenice Bernal-Enriquez; Pedro Madinabeitia-Rodríguez; Kenia Nahomi Morales-Medino; Cynthia Roque-Ibanez; Mario Raúl Hernandez-Zavala (Indian Journal of Rheumatology)
Background: Special attention has been paid to the sequelae caused by SARS-CoV 2 infection (Long-COVID), the prevalence of these sequelae in patients with rheumatological diseases has not been studied in detail. As these patients have immunosuppressive therapy and this syndrome has inflammatory characteristics, we postulate that these patients will have a lower prevalence of sequelae. Methods: We conducted a retrospective, cross-sectional, single-center study in which we interrogated all the patients who had the diagnosis of rheumatological diseases who attended our hospital between August 1, 2021 and November 30 and who had a history of 3 or more months of SARS CoV2 infection. The interrogation consisted of a brief questionnaire on the persistence of symptoms 3 months after the event. Results: We included 64 patients: 19 patients with rheumatoid arthritis (RA), 21 patients with systemic lupus erythematosus (SLE), and 24 with other rheumatological diseases. Long COVID symptoms reported were similar to those described in the literature of patients without rheumatic diseases. The prevalence of fatigue was significantly lower in SLE compared to RA and the rest of the pathologies, but there were no other significant differences between them. Conclusions: The long COVID syndrome is common in patients with and without rheumatic diseases, and the prevalence of each of these symptoms differs little between these groups. A lower prevalence of post-COVID symptoms was seen in patients with SLE than in the rest of the rheumatological diseases, but after we run a binary logistic regression model, most of these differences were not significant and they did not differ much from the general population.